Colecistectomía y esplenectomía laparoscópica simultánea en un paciente con anemia hemolítica por esferocitosis. - NUÑEZ HUERTA, Edgar (2015)
We describe the surgical management of a patient who had gallbladder stones and hemolytic anemia by spherocytosis. On this patient we performed cholecystectomy and splenectomy by laparoscopic approach without any complications and a succesfully post operative period.